Invitation to heretical reading of Montessori pedagogy - Jarosław Jendza (Problemy Wczesnej Edukacji)
In the article the author invites readers to initiate a certain mode of reading that – inspired by Agamben and Holmes – is called heretical reading. Following the latter, the article suggests that it is important to read Montessori in a heretical way in order to keep this idea open and “alive”. This mode of reading demands constant attempts of playing with the pillars or the main categories of this educational approach. The article is divided into three sections. The first part refers to the socio-historical context of Montessori writings and their reception in Poland. The second part problematizes the issue of dogmatisation and privatization of the knowledge on Montessori and thus making it difficult for the heretical reading to come into being. The last part is devoted to the preliminary sketch of the idea of heretical reading. Following Bourdieu and Agamben the author presents the mode of play – conceived of as an “unappropriate” use of a certain Thing – as a possible initiation of the intellectual experiment that can be called a heretical reading.